Checklist and distribution atlas of the Scarabaeinae (Coleoptera: Scarabaeidae) of Costa Rica - Solís, Ángel; Kohlmann, Bert (Zootaxa, 2012)
The 182 species of Scarabaeinae known to occur in Costa Rica are listed with synonymies included. We place Uroxys mac-rocularis Howden & Young as a synonym of U. boneti Pereira & Halffter (new synonym); we also place Uroxys depres-sifrons Howden & Young as a synonym of U. pauliani Balthasar (new synonym). We conducted a mitochondrial DNAcytochrome oxidase I barcoding analysis in order to clarify some taxonomic uncertainties with Phanaeus pyrois Bates andSulcophanaeus noctis (Bates). We elevate Phanaeus pyrois malyi Arnaud to Phanaeus malyi and revalidate Phanaeus ex-celsus Bates as valid species. We consider the species Dichotomius nevermanni Luederwaldt as incertae sedis. A CostaRican distribution map is provided for all species except Dichotomius costaricensis, which is only known from a countryrecord. We report, map, and estimate the spread of the invasive species Euoniticellus intermedius (Reiche) for Central America, from Chiapas to Costa Rica.